Workshop On Preparing Complementary Foods For Breastfeeding (MP ASI) To Cadres In Stunting Prevention - Umi Hanik; Budhi Setianto; Agus Aan Adriansyah; Merry Susantri; Hartatiek Nila Karmila; Yauwan Tobing Lukiyono; Nikmatus Sa'adah (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Various nutritional problems are found to occur in almost all economic strata of society, both in rural and urban areas. This shows that the underlying cause of these nutritional problems is not only poverty. But also the lack of public knowledge about healthy lifestyles and optimal nutritional fulfilment MPASI is food that can meet nutritional needs so that babies and children are healthy and can grow and develop optimally. Community Service related to the provision of MPASI education. Community service is carried out for cadre mothers in the work area of RW 07, Wonokromo Village, in the form of education related to MPASI for mothers of babies aged 0-1 years, it is hoped that it can increase the knowledge of mothers regarding MPASI so that in the future they can provide MPASI appropriately and well to babies which is useful for fulfilling nutrition as an effort to increase the ideal baby weight or according to the growth curve. Based on the results of the service, counselling on the provision of MPASI according to age and WHO standards as an effort to prevent stunting showed results by the objectives of the activity. Therefore, it is necessary to hold promotive activities in the form of continuous education by forming study groups with mothers of toddlers who are accompanied by cadres. Cadres also need to get supplies and assistance from the Puskesmas Nutrition Team this is expected to help improve the knowledge of mothers who have toddlers in preparing for MPASI so that mothers in Indonesia can play a role in reducing the incidence of stunting. Knowledge transfer can run continuously and in agreement. So that mothers who have babies and toddlers can understand MPASI and can apply it in everyday life. The significance value (2- tailed) of this case example is 0.000 (p <0.05). So that the results of the initial test and the final test experienced significant changes (meaningful). Based on the descriptive statistics of the initial test and the final test, it was proven that the final test was higher. It can be concluded that the Workshop in Preparing MP ASI affects increasing participant knowledge.